PENGELOLAAN SAMPAH BERBASIS KOMUNITAS: INTEGRASI BANK SAMPAH DAN KOMPOSTER EMBER TUMPUK DI DESA KEMPLONG PEKALONGAN - Prayogi, Arditya; Faradhillah, Nadia; Nasrullah, Riki; Kurniawan, Pratomo Cahyo; Berliannanda, Anugrah F.; Pujiono, Imam Prayogo (Sekolah Tinggi Ilmu Ekonomi AMA, 2026)
Organic and inorganic waste management in Indonesia is a major challenge due to the high volume of household waste. In Kemplong Village, Pekalongan, the problem of organic and inorganic waste is exacerbated by a lack of awareness and limited processing facilities, leading to waste accumulation, resulting in pollution and health risks. The Community Service Program (KKN) 62 of UIN Gusdur Pekalongan took the initiative to address this problem by integrating the Waste Bank Unit (BSU) and stacked bucket composters as an integrated solution. The program involved outreach, participation, and practical training during the KKN period, involving the BSU group and housewives. Results showed a reduction in unmanaged waste, increased public awareness, and the production of three active composters, supporting SDG 11. Key challenges include the short duration of the program and reliance on voluntary participation. Strengthening collaboration with local governments is needed for ongoing monitoring, training in marketing recycled products, and the development of waste management infrastructure.